Utilizing whatsapp messenger to enhance listening skills of civil engineering degree students in Mandarin courses at UiTM Penang Branch / Foo Terng Hoe, Teck Heng Lim and Boon Yih Mah - Hoe, Foo Terng (Universiti Teknologi MARA, 2021)
Listening skills are important skills that need to be mastered by foreign language learners. Listening skills have, however, often been neglected in the teaching and learning process. This study aims to investigate the effectiveness of using WhatsApp messenger as an instructional tool in enhancing listening skills. This experimental research employs the two-group pre-test post-test design. Two groups of 30 students who enrolled in the Introductory Mandarin course in one of the public universities in Malaysia took part in the study. During the study, the experimental group of 30 students underwent listening drills and exercises using WhatsApp messenger as the treatment, while another 30 students in the control group were taught by another lecturer using the conventional method of teaching listening skills. Listening test scores of before and after the treatment were compared and analyzed using Independent Samples t-Test to identify the significant level of the difference between the scores of these two groups. The findings show no significant difference in the listening pre-test scores between both control and experimental groups. However, after the treatment, the listening scores of the experimental group students are significantly better than that of the control group students. These results indicate that WhatsApp messenger is a useful instructional tool to teach listening skills in foreign language. The findings of this study could be used as a reference for further development of WhatsApp messenger as an instructional tool to enhance listening skills, overcome the constraints on teaching time, and improve the pedagogy as well as the instructions of foreign language learning.